2021
DOI: 10.1007/s10984-021-09361-2
|View full text |Cite
|
Sign up to set email alerts
|

Learning environments’ influence on students’ learning experience in an Australian Faculty of Business and Economics

Abstract: We investigated how learning environments–involving their physical, pedagogical, and psychosocial dimensions–influence students learning experiences in an Australian Faculty of Business and Economics. Qualitative data collection involved observations of eight classrooms over a semester, four focus groups with 21 students and interviews with six educators. The study provided deeper understanding of the dynamic and complex intrinsic interrelations of learning environment dimensions over time, addressing previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 34 publications
1
24
0
2
Order By: Relevance
“…This indicated that there were few laboratories for practical work to be done in schools in order for students to perform well in examinations by mean score of 2.29. This finding was concurred with the study of Closs et al (2021), who observed that students understand well when teachers teach practically. Therefore, having enough laboratories reduce the tendency of teachers to teach theoretically and take students to laboratories for practical work.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This indicated that there were few laboratories for practical work to be done in schools in order for students to perform well in examinations by mean score of 2.29. This finding was concurred with the study of Closs et al (2021), who observed that students understand well when teachers teach practically. Therefore, having enough laboratories reduce the tendency of teachers to teach theoretically and take students to laboratories for practical work.…”
Section: Resultssupporting
confidence: 90%
“…The main scope of empirical reviews on this study was to review different studies on school physical facilities in order to identify how school physical facilities influence students' academic performance in form four national examinations. Closs et al (2021), conducted a study on Learning Environments' Influence on Students Learning Experience in an Australian Faculty of Business and Economics and identified that classroom size, furniture, technology, laboratories and library rooms have a great influence on students' academic performance.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…According to Erikson's theory of psychosocial development and more recent variations, this is a period of major change as young adults develop their own identities [6,7]. Shifts in attitudes, beliefs, values, and behaviours can Keywords: Transformational Learning Theory, medical education, preclinical international rural placement, career choice, role models, rural healthcare be facilitated by removing learners from their routine environment [8], placing them in situations 'at the edge of their understanding' [9][10][11]. A total of 65 students received a Bursary between 2001 and 2019.…”
Section: Organisational Context-interventionmentioning
confidence: 99%
“…According to Erikson’s theory of psychosocial development and more recent variations, this is a period of major change as young adults develop their own identities [ 6 , 7 ]. Shifts in attitudes, beliefs, values, and behaviours can be facilitated by removing learners from their routine environment [ 8 ], placing them in situations ‘at the edge of their understanding’ [ 9 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Savukārt cilvēka ekoloģijā, t.sk. izglītības ekoloģijā, balstoties uz ekoloģiski daudzdimensionālo pieeju, tiek izdalītas vairākas vides dimensijas, ko daudzi autori sauc arī par vides komponentiem un arī par vides kontekstiem (Closs, Mahat, & Imms, 2021;Hiemstra, 1991;Katane, 2007;Katane & Katans, 2014;Radcliffe, 2008 Balstoties uz iepriekš teikto, autores ir izdalījušas skolas jauniešu valsts aizsardzības izglītības vides četras dimensijas jeb kontekstus (2.att. ): militārās izglītības vides dimensija; 2) pilsoniskās izglītības vides dimensija; 3) izglītības vides informatīvi tehnoloģiskā dimensija; 4) izglītības vides psiholoģiskā dimensija.…”
Section: Lai Veidotos Jaunā Domāšana Vērtībās Balstītās Attieksmes Un...unclassified